2012
DOI: 10.1111/j.1464-5491.2012.03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Would sickle cell trait influence the metabolic control in sub‐Saharan individuals with type 2 diabetes?

Abstract: Sickle cell trait was as frequent in this subgroup of patients with Type 2 diabetes as in the general population, suggesting no specific association with diabetes. It does not affect the metabolic control of diabetes. However, how this translates into long-term outcome needs to be fully elucidated in this setting, with an increasing population with both sickle cell trait and diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…This is in contrast to another study among Africans, which did not find any association between type 2 diabetes mellitus (T2D) and SCT. The study observed that the prevalence of 19% for SCT among the patients is comparable with the prevalence in the general population [13] . Another study in African Americans concluded that SCT does not increase the risk of microvascular complications.…”
Section: Type 2 Diabetes Mellitussupporting
confidence: 55%
See 1 more Smart Citation
“…This is in contrast to another study among Africans, which did not find any association between type 2 diabetes mellitus (T2D) and SCT. The study observed that the prevalence of 19% for SCT among the patients is comparable with the prevalence in the general population [13] . Another study in African Americans concluded that SCT does not increase the risk of microvascular complications.…”
Section: Type 2 Diabetes Mellitussupporting
confidence: 55%
“…Nigeria probably has the highest number of people with the trait, not just because of its high population but also because of a high prevalence of 25-30% [9] . The distributions in other parts of Africa are between 10-15% for Liberia, Ghana and Uganda [10][11][12] , respectively, Cameroon and the Republic of Gabon, a central African country, have a prevalence of 19 and 22%, respectively, closer to the prevalence in Nigeria than to other African countries [13,14] . Review of data from two decades of newborn screening in the United States revealed a prevalence of 1.5% [15] , but the prevalence in African Americans is about 8% [16] , which is similar to that of other African populations who migrated out of Africa as a result of the slave trade.…”
Section: Epidemiologymentioning
confidence: 99%
“…A recent study from Cameroon has provided findings suggesting similar frequencies of sickle cell trait (SCT) in people with diabetes and in the general population,42 and that the presence of SCT did not affect the metabolic control of diabetes. A striking fact in this study, however, was the older age of patients with SCT, for a comparable duration of diagnosed diabetes with the non-trait patients, indicating a possible late onset of type 2 diabetes in SCT carriers.…”
Section: Concurrent and Comorbidities Of Diabetes In Africamentioning
confidence: 99%
“…Clarifying a possible link between SCT and diabetes onset or early attrition in diabetes is important in Africa, where the largest number of people with SCT and sickle cell disease (SCD) are found. The growing population with diabetes in Africa will likely include more people with both diabetes and SCT/SCD, and may result in differential features of diabetes across the continent, since the majority of those with SCT/SCD are typically found in Equatorial Africa, the epicentre of the disease 42. Resolving this uncertainty may invite efforts beyond what a single country can achieve.…”
Section: Concurrent and Comorbidities Of Diabetes In Africamentioning
confidence: 99%
“…Liberia, Ghana and Uganda have 10–15% of their population being carriers of haemoglobin S gene [13, 15, 16]. Cameroon and Gabon have haemoglobin S gene prevalence of 19 and 22%, respectively [17, 18]. SCT individuals are clinically healthy to donate blood [19].…”
Section: Introductionmentioning
confidence: 99%